Faktor Pembangun Citra yang Mempengaruhi Keputusan Masyarakat Memilih Walikota Depok Saat Pandemi Covid 19 - Mohammad Alfi Aldaena; Cholifah Cholifah; Indiana Ngenget (Neolectura, 2023)
This article is the result of research on the Simultaneous Pilkada in Depok City December 2020. The aim of the research is to measure the factors that influence the decisions of the people of Depok City (Sukmajaya Village RT 01 and RW 02) in choosing based on their political preferences. Data was collected through a questionnaire on 360 respondents from a total population of 3,262 people in 2 RWs. The theory used is political communication, voting decisions and the concept of candidate image and information sources. The results of the study show that from the 28 statements 9 factors are formed, namely the Mass Media factor, the leader's ability and experience factor in dealing with Covid-19, the leader factor who has a view of the future, the leader's ability factor in carrying out work programs, the community's interest factor in the leader's way of handling Covid-19, the New Media Source factor, the leader's capability factor in conducting supervision, the leader's skill factor and the leader's ability factor in implementing health protocols. In conclusion, the most dominant factor is the Mass Media which influences people's decisions in choosing the Depok Mayor in the December 2020 Pilkada.